Playing with (wild)fire : a novel - Pritchett, Laura, 1971- (Torrey House Press, 2024)
"When a wildfire bears down on a mountain community, residents are forced to gather for safety--resulting in a tangle of love and lust that pulls people from their isolation, friendships that form across political divides, and a new hope for rethinking the ways humans inhabit the burning planet. Playing with Wildfire is a literary landscape that is an experiment in form: an astrology report; a grant application-turned-love-story; a phone call from Mother Earth; an obituary for a wildfire; a burned mountain's conversation with a lone woman and an injured bear. Every story captures how fire affects the human psyche and life, and how destruction can lead to renewal" --